PENGARUH MODEL PEMBELAJARAN DARING (DENGAN PEMUTARAN VIDEO) TERHADAP PEMAHAMAN KONSEP TERJADINYA BENCANA ALAM (KEBAKARAN DAN GEMPA BUMI) PADA INSTITUSI PENDIDIKAN KESEHATAN “X” DI KOTA SURABAYA - M. Usa, WD. Yuni; Andreas Pradhana; Juni Dwi Kurnia Santi; Enny Mar’atus Sholihah; Vebiola Dammu Djari; Anisa Nomeni; Kifri Aquinas (Jurnal Medicare, 2025)
Online learning is an alternative way to improve the effectiveness of understanding a concept. The purpose of this study was to determine the effect of the online learning model using video playback on the understanding of the concept of natural disasters (fires and earthquakes) in students of the health education institution "X" in Surabaya. The method used was quantitative with a pre-experimental design in the form of one group pretest-posttest. The research sample was students of the health study program with a total of 110 respondents. Data through a test of understanding the concept of natural disasters before being given online learning based on video playback and after the online learning was completed. The analysis of the results showed a significant increase in the understanding of the concept of respondents after participating in learning which was supported by the results of the T-Test statistical test with a value of 0.000 (ρ <0.05). These results indicate that the use of video as a medium in online learning can improve students' understanding of the concept of natural disasters (fires and earthquakes) so that it can be an effective strategy in the learning process in the digital era.